A MAPPING STUDY ON OCEANOGRAPHY FROM 2015 TO 2019: A SCIENTOMETRIC STUDY - A. , Ganesa Murthy; K. , Kannan (International Journal of Psychosocial Rehabilitation, 2020)
The present study investigates a Mapping Study on Oceanography from 2015 to 2019: A Scientometric Study. The oceanography is essential in the blue revolution of agriculture and related fields. The data have been extracted from the Scopus database by using the key term of oceanography. The selected period for study is five years (2015-2019). Totally 19,316 publications were found in the period, and the majority of the publications were in 2019. The relative growth rate in 2016 increased (0.72) and the minimum in 2019 was 0.25 decreases. It shows the result of maximum 1.11 and annual growth rate was recorded in the year 2017, a minimum of 0.98 ARoG in the year 2018. In the author-wise analysis, it is found that Xie, S.P., has published 46 publications. In the selected period, 74.02 percent of publications were articles, and others were only 73.27. In the topic-wise analysis, publications on Earth and Planetary Sciences were more in number, which are 13443 (69.60%).